Heat‐acclimatization and pre‐cooling: a further boost for endurance performance?. (17th December 2015) - Schmit, C.; Le Meur, Y.; Duffield, R.; Robach, P.; Oussedik, N.; Coutts, A. J.; Hausswirth, C.
Abstract : To determine if pre‐cooling (PC) following heat‐acclimatization (HA) can further improve self‐paced endurance performance in the heat, 13 male triathletes performed two 20‐km cycling time‐trials (TT) at 35 °C, 50% relative humidity, before and after an 8‐day training camp, each time with (PC) or without (control) ice vest PC. Pacing strategies, physiological and perceptual responses were assessed during each TT. PC and HA induced moderate (+10 ± 18 W; effect size [ES] 4.4 ± 4.6%) and very large (+28 ± 19 W; ES 11.7 ± 4.1%) increases in power output (PO), respectively. The overall PC effect became unclear after HA (+4 ± 14 W; ES 1.4 ± 3.0%). However, pacing analysis revealed that PC remained transiently beneficial post‐HA, i.e., during the first half of the TT. Both HA and PC pre‐HA were characterized by an enhanced PO without increased cardio‐thermoregulatory or perceptual disturbances, while post‐HA PC only improved thermal comfort. PC improved 20‐km TT performance in unacclimatized athletes, but an 8‐day HA period attenuated the magnitude of this effect. The respective converging physiological responses to HA and PC may explain the blunting of PC effectiveness. However, perceptual benefits from PC can still account for the small alterations to pacing noted post‐HA.